PENGEMBANGAN PRODUK ANTISEPTIK LUKA BAKAR BERBASIS BAHAN ALAM (DAUN TEMBELEKAN) PADA MASYARAKAT RT 1 LOLU SELATAN, SULAWESI TENGAH - Magfirah, Magfirah; Purwantari, Anita; liska, Iluh (Jurnal Abdi Insani, 2025)
Early treatment of burns using natural ingredients such as tembelekan leaves quickly and appropriately can accelerate the healing process and prevent more serious injuries. However, based on a common phenomenon in the community, there are still many inappropriate behaviors in providing first aid for burns. This community service activity aims to increase public knowledge about the use of tembelekan leaves as first aid for burns. The methods used in this activity include socialization through counseling, which is then followed by a discussion session, questions and answers, and the distribution of questionnaires to measure the level of community satisfaction with this community service activity. The community service activity was carried out on July 26, 2025, with the main target community in the South Lolu Village area, especially RT 01. The results of the evaluation of community satisfaction with an average satisfaction level of 89.86%. Aspects assessed included the method of delivering materials used in the Community Partnership Program (PKM), the suitability of the program to community needs, improving community thinking skills, the usefulness of the program that can be applied in daily life, and the community's willingness to participate in similar activities again in the future. It can be concluded that the Community Partnership Program (PKM) activity is very beneficial for the people of South Lolu Village, especially in RT 01, because it is able to increase knowledge, skills, and active participation of the community in the initial treatment of burns by utilizing natural materials such as tembelekan leaves.